From Paris to Pompeii French Romanticism and the Cultural Politics of Archaeology - Blix, Göran (University of Pennsylvania Press, 2013)
Through the iconic example of Pompeii, and the spell this city cast on the early nineteen-century French Romantic imagination, From Paris to Pompeiishows how an archaeological gaze arose in response to a secular anxiety of memory loss and helped define our modern relationship to history.